Integration of augmented reality technology to enhance English speaking skills for tourism industry employees in Sumbawa regency - Umar, Umar; Yuliadi, Yuliadi; Hidayatullah, Muhammad (Edelweiss Applied Science and Technology, 2024)
The integration of Augmented Reality (AR) technology into language learning has gained attention due to its potential to enhance speaking skills in practical contexts like the tourism industry. This study examines the long-term effectiveness of AR in improving English speaking skills fluency, accuracy, pronunciation, and grammar among tourism employees in Sumbawa Regency. The researchers developed VirtuoBot, an AR-based learning platform designed to simulate real-world interactions through interactive dialogues. A mixed-methods approach was used to assess the impact of AR-based language training on speaking proficiency. 90 participants from four major tourist sites took part in pre-and post-tests, supplemented by qualitative interviews. Results showed significant improvements in fluency, accuracy, pronunciation, and grammar after the AR intervention. Challenges like limited access to AR technology and workforce readiness were also noted. This study suggests that AR, through VirtuoBot, is a promising tool for enhancing English speaking skills in tourism, contributing to better service quality. Further research is recommended to address accessibility challenges and optimize AR training methods, ensuring sustainable implementation and broader adoption in tourism sectors of developing regions like Sumbawa.